The diversity of spring hexaploid triticales, differing on the time of the onset of developmental phases under conditions of near Ob region of Western Siberia - M. V. Emtseva; P. I. Stepochkin (Вавиловский журнал генетики и селекции, 2016)
The time of the onset of developmental phases of 78 spring hexaploid triticale samples from the world collection of N.I. Vavilov Institute of Plant Industry is studied under natural conditions, in two replicates with a 18-day interval between two dates of sowing. The number of days from the date of sowing up to the date of heading of triticale samples at the I term sowing was from 31 to 49, and at the II term sowing, from 30 to 52. Samples from Argentina, Portugal, Eastern Europe, Poland, Belarus, and Ukraine headed within the interval of mean values (34–40 days). Triticale M2A/Cin from Ethiopia was relatively early ripening. Late ripening were the samples from Zambia, Brazil, North America. Among triticales from Mexico, Dagestan and Russia both early and late ripening forms occurred. Most samples (82 %) at the II term sowing headed 1–9 days earlier than at the I term sowing, which was probably due to a shortening of the period «shoots– the first node» by 1–7 days in 87 % of samples. After lengthening this period, in the triticales studied in the present work, as in wheat, the length of vegetation period increased. The length of the interphase period «heading– ripening» in these samples increased, while in wheat some authors noticed its shortening. Hexaploid triticale samples studied had different times of the onset of developmental phases and response to different terms of sowing, which means their possible use in regions with different daylength.